System-level reliability enhancement of DC/DC stage in a single-phase PV inverter. (September 2018) - Peyghami, Saeed; Davari, Pooya; Wang, Huai; Blaabjerg, Frede
Abstract: This paper studies the impact of modulation scheme, mission profile and PV array configuration on the reliability of a double-stage single-phase PV inverter. A single-phase double-stage inverter with two boost-based Maximum Power Point Tracker (MPPT) is considered and the reliability of dc/dc stage is estimated under different mission profiles. Furthermore, two types of PV panels with different output characteristics are considered to demonstrate the impact of PV array design on the PV converter reliability. Moreover, a phase shifted-switching scheme for the dc/dc converters and inverter is proposed to improve the overall reliability. The outcome is the PV converter reliability enhancement through suitable PV panel selection and proposed phase-shifted modulation scheme, which can be a system-level design for reliability guideline for PV converter and PV system designers.